Association and description of the male of Aplochares imitator (Smith) (Hymenoptera: Pompilidae) - Pitts, James P.; Sadler, Emily (Zootaxa, 2017)
The previously unknown male of Aplochares imitator (Smith), the type species of the genus, is associated with the female and described. Aplochares imitator provides another case of dual sex-limited mimicry. The coloration of the male of A. imitator is similar to that of both sexes of A. adrastes Banks, while the coloration of the female of A. imitator matches that of several species of other unrelated Hymenoptera. A key to both sexes of Aplochares is provided along with illustrations of the two species.